2012
DOI: 10.1016/j.chom.2012.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Copper in Microbial Pathogenesis: Meddling with the Metal

Abstract: Transition metals such as iron, zinc, copper and manganese are essential for the growth and development of organisms ranging from bacteria to mammals. Numerous studies have focused on the impact of iron availability during bacterial and fungal infections, and increasing evidence suggests that copper is also involved in microbial pathogenesis. Not only is copper an essential co-factor for specific microbial enzymes, but several recent studies also strongly suggest that copper is used to restrict pathogen growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
192
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(204 citation statements)
references
References 82 publications
(119 reference statements)
5
192
0
7
Order By: Relevance
“…The anti-microbial properties of Cu are also used by mammalian host cells as defense mechanisms. For example, Cu plays an important role in innate immune defense to microbial infection in mammals [8,11,12]. Previous studies demonstrated that, upon activation by a pathogen, macrophages elevate the expression levels of high-affinity Cu + importer Ctr1 and P-type Cu ATPase, ATP7A, leading to increased levels of Cu in the phagosome of IFN-γ stimulated macrophages [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The anti-microbial properties of Cu are also used by mammalian host cells as defense mechanisms. For example, Cu plays an important role in innate immune defense to microbial infection in mammals [8,11,12]. Previous studies demonstrated that, upon activation by a pathogen, macrophages elevate the expression levels of high-affinity Cu + importer Ctr1 and P-type Cu ATPase, ATP7A, leading to increased levels of Cu in the phagosome of IFN-γ stimulated macrophages [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Fungal Cu-binding TFs tightly control expression levels of genes involved in Cu uptake and export under Cu-deficient conditions or Cu-excess respectively. In Saccharomyces cerevisiae , Cu importers Ctr1 and Ctr3, located in the plasma membrane, as well as the Cu-MTs Fre1 and Fre7 are activated by the Cu-binding TF Mac1 under Cu-insufficient conditions [8,16]. Under excess Cu, the S. cerevisiae Cu-binding TF Ace1 induces the MT-encoding genes CUP1 and CRS5 , and the Cu/Zn SOD-encoding gene SOD1 [8,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C opper (Cu) is an essential metal for life that serves as a critical cofactor for numerous vital biological processes including oxidative stress resistance, energy production, melanin biogenesis and signal transduction 1,2 . The activities of proteins such as superoxide dismutase, cytochrome c oxidase, dopamine b-hydroxylase and nitrous-oxide reductase depend on Cu 1 .…”
mentioning
confidence: 99%
“…Regarding the use of implants containing copper, practically all clinical experience comes from the use of intrauterine contraceptive devices made of copper [21]. Copper is essential for several cellular enzymatic reactions and plays an important role in hydrogen peroxide (H 2 O 2 ) and highly toxic hydroxyl radical (•OH) generation within phagocytes [2,14,30,34]. This makes copper an interesting material for coating metal implants as a way to prevent periprosthetic infection, especially when considering that copper ions have been shown to have superior antibacterial performance while maintaining biocompatibility in vitro compared with silver, zinc, cobalt, aluminum, and mercury ions [16].…”
Section: Introductionmentioning
confidence: 99%